Complex Symbol “Mind” and the Epistemological Relativism - Mažeikis, Gintautas (Problemos, 1999)
In this article the term “symbol” is defined in the same way as it has been made in neo-Kantian (E. Cassirer), iconological (E. Panofsky) and Gestalt psychology’s (S. Langer) traditions. So, the symbol is a function of thinking which centres various connotation relations in the act of spontaneous perception and expresses the temporary complex unity of discrete phenomena. The symbol “Mind” as a complex unity of different connotations of sense is analysed. There are various emotional states of our understanding connected with this symbol. These emotional states are analysed there as well. Various Weltanschauungs enable the creation of different symbols (relations of connotations) of rationality and of Mind. Every rationality is supported by cultural organizations and institutions of repressions. Comparing with other civilizations and cultures, the history of New Age of European apprehension of symbol “Mind” can’t be considered as the only type of rationality. So, the principle of epistemological relativism is affirmed in this article. The history of rational epistemology is considered from anthropology point of view of cultural and philosophical anthropology. There are short interpretations of various types of symbol “Mind”: “the first cause of movement”, “basis of being”, “force of salvation”, “strenght of harmonizing of cosmos”, “creative power of form of thinking”, “basis of structure of Ego”, “product of connections of neurones”, “expression of social and natural relations”. K. Popper’s conception of the Third Word is criticized there as well.